2018
DOI: 10.1016/j.bbamcr.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic development initiation in the fungus Podospora anserina requires the peroxisome receptor export machinery

Abstract: Peroxisomes are versatile organelles essential for diverse developmental processes. One such process is the meiotic development of Podospora anserina. In this fungus, absence of the docking peroxin PEX13, the RING-finger complex peroxins, or the PTS2 co-receptor PEX20 blocks sexual development before meiocyte formation. However, this defect is not seen in the absence of the receptors PEX5 and PEX7, or of the docking peroxins PEX14 and PEX14/17. Here we describe the function of the remaining uncharacterized P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 88 publications
4
25
0
Order By: Relevance
“…FOX2 is a peroxisomal protein that lacks canonical peroxisometargeting signals (PTS), but whose import into peroxisomes is dependent on the import receptor PEX5. We have shown that FOX2 peroxisome targeting is not affected by the C-terminal tagging (Suaste-Olmos et al, 2018). In addition, for fis1 we corroborated our observations using an ectopically-encoded GFP possessing the consensus peroxisome-targeting signal 1 (GFP-PTS1).…”
Section: Fis1 and Dnm1 Are Required For Peroxisome Divisionsupporting
confidence: 82%
See 4 more Smart Citations
“…FOX2 is a peroxisomal protein that lacks canonical peroxisometargeting signals (PTS), but whose import into peroxisomes is dependent on the import receptor PEX5. We have shown that FOX2 peroxisome targeting is not affected by the C-terminal tagging (Suaste-Olmos et al, 2018). In addition, for fis1 we corroborated our observations using an ectopically-encoded GFP possessing the consensus peroxisome-targeting signal 1 (GFP-PTS1).…”
Section: Fis1 and Dnm1 Are Required For Peroxisome Divisionsupporting
confidence: 82%
“…Streptomyces noursei nat1 gene was obtained from plasmid pAPI509, a derivative from pAPI508 (El-Khoury et al, 2008). Escherichia coli hph gene was obtained from pBC-Hygro (Silar, 1995), P. anserina GPD (glyceraldehyde-3-phosphate dehydrogenase) gene promoter sequence from pPable (Coppin and Debuchy, 2000), and the mCherry-HygR and GFP-HygR cassettes from plasmids pUC-Cherry and pUC-GFP, respectively (Suaste-Olmos et al, 2018). Oligonucleotide primers used in this research are shown on Supplementary Table 2. Gene Sequences FIS1 (Pa_3_3970), DNM1 (Pa_1_12670), ATP9-7 (Pa_7_20), and IDH1 (Pa_1_5850) sequences were obtained from the P. anserina genome sequence (Espagne et al, 2008).…”
Section: Nucleic Acid Isolation Transformation and Plasmidsmentioning
confidence: 99%
See 3 more Smart Citations